2018
DOI: 10.1101/355958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roles of motion perception and visual acuity for driving hazard perception

Abstract: PURPOSEThere are many visually impaired people who can drive legally with bioptic telescope. Drawing on the experience of drivers with reduced vision, this study investigated the role of motion perception and visual acuity in driving, under simulated low visual acuity.METHODSTwenty normally sighted participants took part in a driving hazard perception (HP) test, in four different conditions: with/without motion interruption and with/without simulated low visual acuity. In interrupted motion conditions a mask f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous studies have also suggested that motion perception may also play an important role in driving hazard perception. [34][35][36] These visual functions should be evaluated in future naturalistic driving studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that motion perception may also play an important role in driving hazard perception. [34][35][36] These visual functions should be evaluated in future naturalistic driving studies.…”
Section: Discussionmentioning
confidence: 99%